Cash Flow Ratio Analysis as a Measuring Tool for The Company's Financial Performance at PT. Astra International Tbk - Olivia Devi Yulian Pompeng; Jettri Eleonora Rambak (Proceeding of The International Conference on Economics and Business, 2022)
The research question concerns the cash flow ratio as a measure of the company's financial success at PT. Astra Indonesia Tbk during 2018 - 2021. This research aims to examine PT. Astra International Tbk's cash flow ratio as a measure of the company's financial performance for the period 2018-2021. The research methodology employed in this method is descriptive quantitative research, or research techniques that describe data as numerical values. This research provided use of secondary data, mainly information gathered from the official website of the Indonesia Stock Exchange's records or archives. In 2018-2021, a ratio of operating cash flow to current obligations less than one indicates that the situation is not favorable. In 2018-2019, a ratio of operating cash flow to interest payments that is more than 1 is favorable. In 2018-2020, a ratio of operational cash flow to capital expenditure below one indicates that the situation is not good. In 2018-2021, if the ratio of operating cash flow to total debt is less than 1, the situation is not good. In the period between 2018 and 2021, the ratio of operating cash flow to net profit is good since it can exceed 1. The conclusion that can be drawn from the findings of this research is that the results of the five cash flow ratios listed above must still be examined, as values that are above the standard ratio are only 2 ratios and those that are below the standard ratio are 3 ratios. It indicates that PT. Astra International Tbk's financial performance is categorized as poor because it is unable to effectively manage its cash flow, resulting in an insufficient turnover between cash in and cash out so that in the long term PT. Astra will experience losses.